2019
DOI: 10.3390/toxins11020123
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin Light Chains Expressed by Defective Herpes Simplex Virus Type-1 Vectors Cleave SNARE Proteins and Inhibit CGRP Release in Rat Sensory Neurons

Abstract: A set of herpes simplex virus type 1 (HSV-1) amplicon vectors expressing the light chains (LC) of botulinum neurotoxins (BoNT) A, B, C, D, E and F was constructed. Their properties have been assessed in primary cultures of rat embryonic dorsal root ganglia (DRG) neurons, and in organotypic cultures of explanted DRG from adult rats. Following infection of primary cultures of rat embryonic DRG neurons, the different BoNT LC induced efficient cleavage of their corresponding target Soluble N-ethylmaleimide-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The principal mode of action of BoNT/A1 is the cleavage of SNAP25, a component of the SNARE complex necessary for the calcium-mediated vesicular release of neurotransmitters and other proteins. Several studies have confirmed that BoNT/A1 reduces the CGRP release in migraine, its acknowledged pathophysiological mechanism, as well as the release of substance P, one of the major pain-related neuropeptides (Montecucco et al, 1996 ; Purkiss et al, 2000 ; Durham et al, 2004 ; Matak et al, 2017 ; Joussain et al, 2019 ). We endorse previous findings that the terminal nerve endings remain intact after local rBoNT/A1 injection (Paterson et al, 2014 ).…”
Section: Discussionmentioning
confidence: 93%
“…The principal mode of action of BoNT/A1 is the cleavage of SNAP25, a component of the SNARE complex necessary for the calcium-mediated vesicular release of neurotransmitters and other proteins. Several studies have confirmed that BoNT/A1 reduces the CGRP release in migraine, its acknowledged pathophysiological mechanism, as well as the release of substance P, one of the major pain-related neuropeptides (Montecucco et al, 1996 ; Purkiss et al, 2000 ; Durham et al, 2004 ; Matak et al, 2017 ; Joussain et al, 2019 ). We endorse previous findings that the terminal nerve endings remain intact after local rBoNT/A1 injection (Paterson et al, 2014 ).…”
Section: Discussionmentioning
confidence: 93%
“…The first is in vitro animal experiments showing that onabotulinumtoxinA inhibits the release of CGRP from sensory neurons. 50,74 The second is a clinical study showing that onabotulinumtoxinA reduces interictal CGRP plasma levels in chronic migraine patients who are deemed treatment responders but not those deemed treatment nonresponders. 75 In cases in which chronic migraine is associated with chronic muscle tenderness, occipital allodynia, 56,76,77 and altered expression of genes related to inflammation in the calvarial periosteum, 56,76,77 extracranial injection of onabotulinumtoxinA may exert its effects through direct action on extracranial nerves (Fig.…”
Section: Migraine Pathophysiology and Onabotulinumtoxina Mechanisms Omentioning
confidence: 99%
“…Distribution of therapeutic gene is governed by the employed viral vector and the application sites. Joussain et al used herpes simplex virus type 1 amplicon vectors to express BoNT LC gene by a non-specific promoter in cultured sensory neurons to inhibit CGRP release [41]. Although herpes simplex virus has tropism to peripheral sensory neurons, it has the risk to penetrate the neuromuscular junction, travel in a pure motor nerve to reach central nervous system motor nucleus [42].…”
Section: Discussionmentioning
confidence: 99%